Pangs of loneliness breed material lifestyle but don't power up life satisfaction of young people: the moderating effect of gender - Ang, Chin Siang; Abu Talib, Mansor; Tan, Kit Aun (Springer, 2014)
Associations between loneliness, materialism, and life satisfaction were examined in a sample of 366 Malaysian undergraduate students. Also examined was the mediating role of materialism in the relation between loneliness and life satisfaction, and such a mediational link (i.e., loneliness–materialism–life satisfaction) is expected to be moderated by gender. Loneliness was significantly and positively associated with materialism but negatively associated with life satisfaction. Materialism was significantly and negatively associated with life satisfaction. In addition to these direct associations, materialism emerged as a significant partial mediator in the relation between loneliness and life satisfaction. As predicted, gender moderated the loneliness–materialism–life satisfaction relationship. In particular, materialism significantly mediated such a link for male undergraduate students but not for female undergraduate students. Theoretical and practical implications of the findings for youth wellness are discussed.